Mixed convection flow of a nanofluid containing gyrotactic microorganisms over a stretching/shrinking sheet in the presence of magnetic field - Aman, Fazlina; Wan Mohamad Khazim, Wan Nor Hafizah; Mansur, Syahira (IOP Publishing, 2017)
Interaction of motile microorganisms and nanoparticles along with buoyancy forces will produce nanofluid bioconvection. Bioconvection happened because of the microorganisms are imposed into the nanofluid to stabilize the nanoparticles to suspend. In this paper, we investigated the problem of mixed convection flow of a nanofluid combined with gyrotactic microorganisms over a stretching/shrinking sheet under the influence of magnetic field. The nonlinear partial differential equations are transformed into a set of five similarities nonlinear ordinary differential equations by using similarity transformation, before being solved numerically. Some of the governing parameters involve in this problem are magnetic parameter, stretching/shrinking parameter, Brownian motion parameter, thermophoresis parameter and Prandtl number. Using tables and graphs, the consequences of numerous parameters on the flow and heat transfer features are examined and discussed. The results indicate that the skin friction coefficient, local Nusselt number, local Sherwood number and local density of the motile microorganisms are strongly affected by the governing parameters.